Trade competitiveness of shrimp products from Malaysia and other selected Asian countries - Ng, Xin Khai (2013)
The Malaysian shrimp industry has been facing competition domestically and internationally. Malaysia‟s export share for shrimp products in the global market has declined in recent years. In fact, the export value for shrimp has also dropped from RM1.3 billion in 2005 to RM1.1 billion in 2009. It is argued that Malaysia cannot be a major player in the world shrimp market because of its relatively small volume of shrimp trade. However, the competitiveness of Malaysian shrimp trade still remains unclear due to the lack of contemporary analyses backed by formal testing procedures. Research objectives of this study are to measure the trade competitiveness of the Malaysian and selected nations‟ shrimp products, and to examine competitiveness growth trends of the selected nations. This study provides evidence on trade competitiveness of the Malaysian and selected nations‟ shrimp products. It is particularly important for Malaysia‟s shrimp commodity because it has been identified as the most traded fishery product of the nation, but has yet to identify the competitive food sub-sectors for import substitution and/or export. There are six individual countries chosen for eleven years of observations. Shrimp products are divided into frozen, non-frozen, and prepared and preserved categories. The reference countries are China, India, Indonesia, Thailand, and the Philippines. This study employs the relative trade advantage (RTA) analysis with secondary data to measure the trade performance in this study. Results from the RTA analysis are then computed using growth trends analysis. Present research exercise has found that Malaysia has comparative disadvantages on shrimp products. However, the comparative disadvantages on non-frozen and prepared and preserved shrimp products have been improving since 2007 to 2009. In fact, the Malaysian frozen shrimp sector is found to be profitable as compared to other food sectors in Malaysia, and it has some extents of competitiveness in the export market. India has a remarkable performance as it has trade competitiveness for all three shrimp products. Thailand is also competitive in non-frozen and prepared and preserved shrimp trade for the period. Policy recommendations have been outlined at the end of the section in order to improve trade competitiveness of Malaysia‟s shrimp products; such as to increase shrimp production for export and domestic markets. This study can be improved by utilizing bilateral trade data and to increase the number of observations. Further analysis on shrimp trade competitiveness by constant market share analysis to be conducted in future study is also worthwhile.